A LEGAL REVIEW BETWEEN IMPACTS OF CHILD SEXUAL ABUSE AND CRIMINAL COMPENSATION ORDER IN MALAYSIA - Izmi Izdiharuddin B Che Jamaludin Mahmud; Nadzriah Ahmad; Rafizah Abu Hassan (Journal of Islamic, Social, Economics and Development, 2022)
In Malaysia, child sexual abuse issues ("CSA") is prevalent even during the Covid- 19 pandemic. In addition, there are numerous social and health issues against child sexual abuse victims ("CSA victims") as it is associated with short and long-term impacts on daily life. Therefore, the compensation may practically assist CSA victims in redressing their sufferings. The primary legislation towards restoring victims' loss or injuries in the Malaysian criminal justice system derives from section 426 (1A) of the Criminal Procedure Code. This provision allows criminal courts to order the offenders to pay a criminal compensation order ("CCO") to victims subject to the application by the public prosecution. Nevertheless, there are shortcomings in the application of Section 426 (1A) due to various reasons, such as the offender does not have the financial ability to pay the compensation, lack of implementation of victims' rights in the criminal justice system, oversight of legal principle of CCO by governmentappointed stakeholders and the system rigidity in the assessment of CCO. Thus, this paper focuses on the relationship between the impacts and availability of compensation for child sexual abuses cases in Malaysia. This research adopts the doctrinal legal research method and will determine whether there is a compensatory justice legal system for CSA victims in Malaysia.